A Tanzanian Boy with Molecularly Confirmed X-Linked Adrenoleukodystrophy - M. C. J. Dekker; A. M. Sadiq; R. Mc Larty; R. M. Mbwasi; M. A. A. P. Willemsen; H. R. Waterham; B. C. Hamel (Case Reports in Genetics)
Adrenoleukodystrophy (ALD) is an X-linked peroxisomal disorder with classical features, which can be also recognised in a low resource setting. It had been described in various populations across the globe, but very few cases have been reported from Africa. In a boy with features of a progressive central nervous system condition and adrenal failure, ABCD1 gene screening was performed based on a clinical history and basic radiological features which were compatible with ALD. A common ABCD1 mutation was identified in this patient, which is the first report of genetically confirmed ALD in Sub-Saharan Africa. ALD is likely under recognised in those areas where there is no neurologist. This genetic confirmation widens geographical distribution of ABCD1-associated disease, and illustrates recognisability of this disorder, even when encountered in a low-resource environment.